Endoplasmic reticulum stress in nonalcoholic (metabolic associated) fatty liver disease (NAFLD/MAFLD). Issue 10 (1st May 2022) - Flessa, Christina‐Maria; Kyrou, Ioannis; Nasiri‐Ansari, Narjes; Kaltsas, Gregory; Kassi, Eva; Randeva, Harpal S.
Abstract: Nonalcoholic fatty liver disease (NAFLD) is characterized by hepatic fat accumulation in the absence of excessive alcohol consumption and is strongly associated with obesity, type 2 diabetes (T2DM) and other metabolic syndrome features. NAFLD is becoming increasingly prevalent and currently constitutes the leading cause of hepatocellular carcinoma (HCC). Recently, the term metabolic (dysfunction) associated fatty liver disease (MAFLD) has been proposed reflecting more accurately the underlying pathogenesis and the cardiometabolic disorders associated to NAFLD/MAFLD. Given the vital metabolic functions of the liver to maintain the body homeostasis, an extended endoplasmic reticulum (ER) network is mandatory in hepatocytes to retain its capacity to adapt to the multiple extracellular and intracellular signals mediating metabolic changes. Dysfunction of hepatocyte ER homeostasis and disturbance of its interaction with mitochondria have been recognized to be involved in the NAFLD pathophysiology. Apart from hepatocytes, hepatic stellate cells, and Kupffer cells have been shown to play an important role in the occurrence of NAFLD and progression to nonalcoholic steatohepatitis (NASH) with possibly different roles in the different stages of the NAFLD spectrum. Furthermore, excess lipid accumulation in the liver causes lipotoxicity which interacts with ER stress and culminates in inflammation and hepatocellular damage, mechanisms crucially implicated in NASH pathogenesis. Finally, the circadian clock machinery regulates ER stress‐related pathways and vice versa, thus controlling the homeostasis of the liver metabolism and being implicated in the NAFLD progression. This review presents a comprehensive overview of the current knowledge supporting the impact of ER stress signaling on NAFLD, whilst summarizing potential therapeutic interventions targeting this process.